An industrial quality control study on a Distilling Company of Ethyl Alcohol - Sumalabe, Marian U. (College of Engineering, 2004)
The Ethyl Alcohol Distilling Company has been known to be a reliable supplier of high quality ethyl alcohol. This study was performed to assess the present production process of the company and to help maintain its high standard and good performance in the distillery industry. The group studied and documented the existing production and quality control system of the company. Using problem identification and analysis tools such as PFMECA and streamline diagnosis diagram, the group identified the problems of the company and was able to observe that many of the problems are related to the quality assurance activities of the company, specifically on the testing procedures for the product and the personnel that handles all such activities. The lack of training for laboratory personnel was perceived to be a contributing factor to the current performance of the laboratory, thus reflecting the performance of the production as well. The group proposed a more rigid and systematic selection and training of laboratory personnel. The group also proposed several laboratory guidelines to aid the personnel in performing their tasks. To further support the need of these personnel to have proper and sufficient training for work, raw data from two quality tests performed by the company's laboratory, purity test and permanganate test, were plotted in control charts. The results of the charts show many out of control points, and these results were also used to analyze the current quality system of the company. It was also recommended that the company should consider the use of control charts as a tool to monitor their process.